2008
DOI: 10.1111/j.1469-7610.2008.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent borderline symptoms in the community: prognosis for functioning over 20 years

Abstract: Adverse prognosis associated with youth symptoms of BPD appeared early and persisted in important and interrelated life domains. These findings lend support to the utility of DSM-IV BPD symptoms assessed by self-report in early adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
164
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(188 citation statements)
references
References 27 publications
8
164
0
16
Order By: Relevance
“…Borderline PD in early adolescence also prospectively predicts low social functioning and life satisfaction, fewer attained adult developmental milestones, and lower academic and occupational attainment, independent of other psychiatric disorders and despite agerelated borderline PD symptom decline over time (74). Finally, PD in adolescence significantly reduces concurrent and future quality of life (124,143), and increases the risk of unnatural and violent death amongst offenders (144).…”
Section: Adverse Outcomes and Adaptive Functioningmentioning
confidence: 99%
See 3 more Smart Citations
“…Borderline PD in early adolescence also prospectively predicts low social functioning and life satisfaction, fewer attained adult developmental milestones, and lower academic and occupational attainment, independent of other psychiatric disorders and despite agerelated borderline PD symptom decline over time (74). Finally, PD in adolescence significantly reduces concurrent and future quality of life (124,143), and increases the risk of unnatural and violent death amongst offenders (144).…”
Section: Adverse Outcomes and Adaptive Functioningmentioning
confidence: 99%
“…Persons displaying PD symptoms below the threshold for a categorical diagnosis are considered to have remitted diagnostically, but they might continue to have clinically significant levels of subthreshold personality pathology. Accordingly studies show that individuals diagnosed with PD in adolescence often still have elevated PD traits in adulthood (46,74). Also, individuals with persistent impairments might change from one diagnostic category to another over time (74), perhaps indicating "heterotypic continuity" -that the underlying developmental and pathological processes remains the same despite changes in phenotypic presentation (16,(75)(76)(77).…”
Section: Continuity and Change In Personality Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the psychic pain, desperation, and high risk for suicide are not typical during this period [9], and research is increasingly demonstrating that BPD can be reliably identified in adolescence, which can permit early and appropriate intervention before symptoms become consolidated [10,11]. Furthermore, research is providing evidence for the contributions of adolescent BPD symptoms to impaired functioning in adulthood, as evidenced by lower life satisfaction, social support and relationship quality, and more chronic stress [12]. As such, examination of BPD symptom development in an adolescent sample can be a reliable opportunity for examining the effects of parental invalidation as it occurs.…”
Section: Introductionmentioning
confidence: 99%